Ensayo comparativo de fertilización fosfórica en el cultivo de maní (Arachis Hipogaea l.) En Morales - Bardales del Aguila, Defilia (1992)
This experiment was carried out in the District of Morales, province and Department of San Martin, in the grounds of the National University of San Martin, located at 350 m.a.s.l. understood to a length of 76 ° 23' and South latitude 06 ° 29 ' with an average temperature of 25° C and a rainfall average of 1,200 mm/year. Soil present the following features textures franca arena, PH 6.0, phosphorus available 3.6 mg/Lt, saturation of aluminum 2.8%. The object of the study was to determine the source and best level of phosphorus for hand cultivation, using rock fosbayovar and triple super phosphate, also carry out economic analysis to its recommendation. It was used to cultivate peanut variety 'white Tarapoto' because they are a very important source of protein in the diet directly and transformed, likewise that it is cultivated traditionally in all the area of the region, still need to find the optimal level of phosphate fertilization in this crop. Planting density was 0.60 m. between Groove and 0.20, between plants, installing in split-plot designs adapted to completely randomized block with 4 replications using levels of 150, 100 and 50 kg / has P2O5 and a witness for both sources. The results obtained show us at the level of sources there is no statistical significance in the first campaign and for factor levels of fertilization there is statistical significance, finding better performance when used 100 kg / has fobayovar rock P2O5. To analyze the benefit/cost of treatments, found that you using the level of 30Kg / has rock P2O5 fosbayovar has obtained an optimal benefit, which was reflected, with less economic benefit when used the super triple phosphate calcium source.